Natural materials : sources, properties, and uses - DeMouthe, Jean Frances (Elsevier/Architectural Press, 2006)
Most museums collections contain a wide variety of natural materials, and a diverse range of knowledge is necessary to keep so many types of objects at their best. This book studies the composition, structure and properties of natural materials such as wood, paper, amber, coral and feathers, and discusses the potential hazards they face, as well as the appropriate conservation techniques to use for each. Providing plenty of detail in an easily accessible format, Natural Materials is a useful resource for students, professionals and collectors alike.